Abnormalities of serum lipid metabolism in patients with acute paraquat poisoning caused by ferroptosis - Lufeng Hu; Qin Lan; Congrong Tang; Jianhui Yang; Xingjie Zhu; Feiyan Lin; Zheng Yu; Xianqin Wang; Congcong Wen; Xiuhua Zhang; Zhongqiu Lu (Ecotoxicology and Environmental Safety, 2023)
As the mechanism of paraquat (PQ) poisoning is still not fully elucidated, and no specific treatment has been developed in medical practice, the management of PQ poisoning continues to present a medical challenge. In this study, the objective was to investigate the early metabolic changes in serum metabolism and identify the key metabolic pathways involved in patients with PQ poisoning. Quantitative analysis was conducted to determine the relevant metabolites. Additionally, experiments were carried out in both plasma and cell to elucidate the mechanisms underlying metabolic disorder and cell death in PQ poisoning. The study found that polyunsaturated fatty acids (PUFAs) and their metabolites, such as arachidonic acid (AA) and hydroxy eicosatetraenoic acids (HETEs), were significantly increased by non-enzymatic oxidative reaction. Reactive oxygen species (ROS) production increased rapidly at 2 h after PQ poisoning, followed by an increase in PUFAs at 12 h, and intracellular glutathione, cysteine (Cys), and Fe2+ at 24 h. However, at 36 h later, intracellular glutathione and Cys decreased, HETEs increased, and the expression of SLC7A11 and glutathione peroxidase 4 (GPX4) decreased. Ultrastructural examination revealed the absence of mitochondrial cristae. Deferoxamine was found to alleviate lipid oxidation, and increase the viability of PQ toxic cells in the low dose. In conclusion, unsaturated fatty acids metabolism was the key metabolic pathways in PQ poisoning. PQ caused cell death through the induction of ferroptosis. Inhibition of ferroptosis could be a novel strategy for the treatment of PQ poisoning.